"The beautiful language of my century" : reinventing the language of contestation in postwar France, 1945-1968 - McDonough, Tom, 1969- (MIT Press, 2007)
How culture became a field of struggle over meaning in France: the appropriation of elements from advertising, journalism, and other sources to serve political ends in art, film, and the activities of the French left, culminating in the upheavals of May 1.